Evolusi Peran Gender dalam Dinamika Politik Lokal: Studi Perempuan dalam Pemilihan Kepala Daerah 2024 - Puji Lestari; Erisandi Arditama; Zuraini binti Jamil; Supraptiwi Supraptiwi (Universitas Hamzanwadi, 2025)
This research explores the shift in gender construction identified in the dynamics of local politics in Central Java, specifically during the 2024 regional head elections. The pluralist perspective on local political studies emphasizes the inevitability of diverse local actors in managing power at the local level, including for local women. This research was carried out with a descriptive qualitative approach to analysis chosen in this study, because it aims to explore in-depth understanding of social and political phenomena, namely shifts in gender construction in local political dynamics in Central Java. Data was extracted through in-depth interviews and document data. Interviews with female informants of regional head candidates in Central Java, success teams, and voters, in the simultaneous regional head elections, were conducted to explore perceptions, views, and experiences so that they could interpret freely. The interviews used purposive sampling techniques, both in person and with messages through social media to voters in Central Java. The results of the study identified the phenomenon of gender construction evolution; first, shifting beliefs, values about women who are increasingly ready, have the ability in politics, so that they get validation and recognition from the voting community; second, political party support, ownership of women's financial capital in politics; and third, women's ability to face challenges that arise from themselves. Self-confidence in facing social pressure, political pressure, and political pressure is one of the most important factors.